2006
DOI: 10.1007/s10620-006-9554-x
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome Assessment of Double-Balloon Enteroscopy for Diagnosing and Managing Patients with Obscure Gastrointestinal Bleeding

Abstract: Diagnosing and treating patients with obscure gastrointestinal bleeding is clinically challenging. Most lesions responsible for the origin of obscure gastrointestinal bleeding are located in the small bowel. Double-balloon enteroscopy is a novel method for exploring the small intestine and has significant therapeutic potential. This study evaluated the value of double-balloon enteroscopy in diagnosing and managing obscure gastrointestinal bleeding. From October 2003 to January 2006, a total of 20 patients (6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Seventy-seven percent of patients maintained a normal haemoglobin. Hsu et al [59] similarly found significantly less rebleeding in patients who were treated for an identified lesion when compared to patients in whom no lesion was found (20% vs 80%).…”
Section: Capsule Endoscopymentioning
confidence: 93%
See 1 more Smart Citation
“…Seventy-seven percent of patients maintained a normal haemoglobin. Hsu et al [59] similarly found significantly less rebleeding in patients who were treated for an identified lesion when compared to patients in whom no lesion was found (20% vs 80%).…”
Section: Capsule Endoscopymentioning
confidence: 93%
“…It is considered the gold standard for therapeutic intervention of many small bowel disorders in OGIB [49] . The diagnostic yield and treatment success of DBE for OGIB in published literature ranges from 60%-81% and 43%-84% respectively [10,[50][51][52][53][54][55][56][57][58][59][60] . The variation in diagnostic yield is a result of differences in DBE timing, inclusion criteria and definitions of a significant finding [61] .…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…Temporary endoscopic hemostasis for surgical candidates to avoid emergency operation is another application of DBE [15,16]. Staged surgical intervention after DBE offers critically ill patients an invaluable period during which blood transfusion, fluid and electrolyte supplementation, nutritional support, correction of underlying medical diseases, and supplementary workup can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Both the enteroscopic device and the double-balloon technique, which allows the small bowel to be threaded onto the overtube, has been described in detail elsewhere [15,16]. The insertion route was determined by the endoscopists based on the clinical presentation and the results of previous investigations.…”
Section: Methods For Dbementioning
confidence: 99%
“…In published studies, doubleballoon enteroscopy has displayed superior diagnostic yield and therapeutic power for obscure gastrointestinal bleeding [1,16]. The primary aim of this study is to assess the diagnostic and therapeutic yield in obscure gastrointestinal bleeding.…”
Section: Introductionmentioning
confidence: 99%